PENGARUH PEMBELAJARAN BERBASIS WEBSITE "WEBYMOM" TERHADAP MATERNAL SELF-EFFICACY PADA IBU POSTPARTUM SELAMA PANDEMI COVID-19 - Ni Made Anggun Millenia (2022)
The COVID-19 pandemic can worsen the psychological condition of postpartum mothers, where this can have an impact on decreasing maternal self-efficacy in the postpartum period. Efforts to increase maternal self-efficacy can be done with health education. The purpose of this study was to determine the effect of website-based learning "WEBYMOM" on maternal self-efficacy in postpartum mothers during the COVID-19 pandemic. The research design used in the study was a quasi-experimental with one group pre and post test on 42 postpartum mothers with total sampling technique. The instruments in this study include a demographic data questionnaire and a maternal self-efficacy questionnaire (MSQ), and the data that has been collected is then analyzed using the McNemar test. The results showed that there was a significant effect on the provision of website-based learning "WEBYMOM" on maternal self-efficacy of postpartum mothers during the COVID-19 pandemic (p-value = 0.002). It is recommended that health service providers provide more health education, especially postpartum education for mothers in the postpartum period.